ANALISIS PENANGANAN PENGARUH KERUSAKAN JALAN NASIONAL AKIBAT MUATAN BERLEBIH DI PROVINSI LAMPUNG - Tosulpa, M. Enriko; Putranto, Leksmono S; Sulistyorini, Rahayu (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
Lampung Province, as the land gateway between Sumatra and Java, plays a vital role in Indonesia’s national road network. With 1,298 km of national roads managed by BPJN Lampung, the region supports high traffic from heavy vehicles. However, these roads face significant damage, primarily due to two factors: poor road management (including planning, execution, supervision, and maintenance) and the frequent passage of ODOL (Over Dimension Over Loading) vehicles. This study investigates the causes and key parameters of road damage in Lampung, aiming to identify the most dominant factors. Data were obtained from interviews, questionnaires, and road section records from relevant stakeholders and analyzed using the Analytic Hierarchy Process (AHP). The findings reveal that ODOL vehicles are the most significant cause of road damage, with a weight of 67%, while the International Roughness Index (IRI) emerged as the most critical parameter, holding a weight of 27%. These results underline the urgent need for tighter regulations on ODOL traffic and the prioritization of IRI as a core measure in assessing road quality. Enhancing monitoring and maintenance based on these insights is essential to improving road durability and ensuring sustainable transportation in Lampung Province.